Free radical-scavenging capacity, antioxidant activity and phenolic content of Pouzolzia zeylanica - Li, Peiyuan; Huo, Lini; Su, Wei; Lu, Rumei; Deng, Chaocheng; Liu, Liangquan; Deng, Yongkun; Guo, Nana; Lu, Chengsheng; He, Chunling (Journal of the Serbian Chemical Society, 2011)
Pouzolzia zeylanica was extracted with different solvents (acetone, ethyl acetate and petroleum ether), using different protocols (cold-extraction and Soxhlet extraction). To evaluate the antiradical and antioxidant abilities of the extracts, four in vitro test systems were employed, i.e., DPPH, ABTS and hydroxyl radical scavenging assays and a reducing power assay. All extracts exhibited outstanding antioxidant activities that were superior to that of butylated hydroxytoluene. The ethyl acetate extracts exhibited the most significant antioxidant activities, and cold-extraction under stirring seemed to be the more efficacious method for acquiring the predominant antioxidants. Furthermore, the antioxidant activities and total phenolic (TP) content of different extracts followed the same order, i.e., there is a good correlation between antioxidant activities and TP content. The results showed that these extracts, especially the ethyl acetate extracts, could be considered as natural antioxidants and may be useful for curing diseases arising from oxidative deterioration. nema